THE ROLE OF HOSPITALITY IN STRENGTHENING FRIENDSHIP BETWEEN NATIONS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the role of hospitality in strengthening friendship between nations living in unity and harmony. The traditions of hospitality of the Kyrgyz people are an important element of their national culture, which has existed since ancient times. It is noted that hospitality is not only a symbol of respect and goodwill, but also serves as an important social mechanism that helps establish trusting relationships between representatives of different nationalities. Historically, in Kyrgyz society, guests were perceived as messengers of good, regardless of nationality or social status. Reception of guests is always accompanied by special respect, hospitality and delicious food. The article provides a detailed analysis of various categories of guests, the peculiarities of their reception, as well as the significance of this tradition in the modern world. The traditions of hospitality played a key role in strengthening interethnic harmony, contributed to the maintenance of peace, friendship and mutual understanding between peoples. In the context of globalization, hospitality is becoming an important tool for overcoming cultural differences, developing and strengthening international relations.
Keywords: hospitality, Kyrgyz culture, traditions, respect, national identity, attitude, peace, unity.